Preliminary results from the paleomicrobiological studies of Mycobacterium tuberculosis infection in the Bácsalmás-Óalmás anthropological series - Neparáczki, Endre (Acta Biologica Szegediensis, 2011)
The aim of the actual study of the 16-17th centuries AD series of Bácsalmás-Óalmás (Hungary) is to combine the osteological and complete paleomicrobiological studies of a large series of approximately half a thousand skeletons. This material, which is stored in the collections of the Department of Biological Anthropology, University of Szeged, was chosen because of the good state of preservation and of some previous aDNA results. Some cases of TB infections have already been confirmed during the analysis of the first third of the series. In the actual state of the Bácsalmás ancient TB project, a general morpho-pathological study of the complete series is in progress in the frame of a PhD thesis at the University of Szeged. Molecular paleomicrobiological analysis to diagnose bacteria of the Mycobacteria tuberculosis complex has been initiated in the ancient DNA Laboratory of the Institute for Mummies and the Iceman, EURAC Research, Bolzano, Italy. A PCR-based assay targeting the multicopy IS6110 region has been conducted to a subset of the samples. First results already indicate the presence of Mycobacteria in some of the rib samples. These positive cases will be further subtyped via Spoligotyping.